Invasion status and risk assessment for Salvia tiliifolia, a recently recognised introduction to China. (14th June 2013) - Hu, G X; Xiang, C L; Liu, E D
Summary: This study corrected the misidentification of an alien species, Salvia tiliifolia, which had been incorrectly identified as S. dugesii (a synonym of S. melissodora ) in China. The distribution of S. tiliifolia in China was surveyed and it was inferred that it was probably introduced into Kunming, Yunnan in the 1990s and then spread to adjacent counties of Yunnan and south‐western Sichuan Province. The Australian weed risk assessment (WRA) was used to evaluate its invasive status. To determine the validity of Australian WRA in China, another 25 exotics representing casual alien plants, naturalised plants and invasive plants were tested. The Australian WRA was validated as a legitimate approach in China. Salvia tiliifolia scored 14, falling into the category of invasive plants. While the distribution of S. tiliifolia is currently restricted to Yunnan and a small part of Sichuan and the species has not displayed an adverse impact on local environments yet, the WRA results indicated that the species was a high risk plant. It was recommended that local land managers should monitor this species and take measures to stop its continuing expansion or eradicate it if possible.